The State of Emergency in Indonesia. A Great Lesson from the Covid-19 Pandemic - Claudia Siwu, Sonya; Aulia Rahman, Rofi (KnE Social Sciences, 2022)
The Covid-19 pandemic is interpreted by the President as a public health emergency (KEPPRES No. 12 of 2020). None of those declarations refers to either Article 12 or Article 22 of the 1945 Constitution of the Republic of Indonesia, although the situation (de facto) meets all the criteria of a state of emergency. On behalf of justice, normal law shall be applied in a normal situation, while in an abnormal situation, an abnormal law shall be applied. Regarding that issue, this paper investigates these three questions: i) why is the state of emergency not applied in the time of Covid-19? ii) how to measure the scale of the emergency of Covid-19 pandemic from the perspective of the state of emergency? iii) how should the law of the state of emergency in Indonesia overcome the situation in the future? These questions would be discussed on the level of legal philosophy using legal politics approach, statutory approach, conceptual approach, theoretical approach, and comparative approach. The main principle is solus populi suprema lex. It should be implemented properly. The results of this study indicate and explain that the state emergency law must adhere to the concept of people’s security is state security. In addition, state emergency laws must be anticipatory to new and very diverse developments and forms of danger. Keywords: state of emergency, political legal dimension, future legal framework, legal reform